Impact of Coexisting Pulmonary Diseases on Survival of Patients With Lung Adenocarcinoma. Issue 4 (January 2015) - Jian, Zhi-Hong; Huang, Jing-Yang; Ko, Pei-Chieh; Jan, Shiou-Rung; Nfor, Oswald Ndi; Lung, Chia-Chi; Ku, Wen-Yuan; Ho, Chien-Chang; Pan, Hui-Hsien; Liaw, Yung-Po; M Langevin., Scott
<x xml:space="preserve">Abstract</x> Abstract Asthma, chronic obstructive pulmonary disease (COPD), and pulmonary tuberculosis (TB) are common pulmonary diseases associated with lung cancer. Besides, smoking is more prevalent in Taiwanese men. This study evaluated gender disparities in coexisting pulmonary diseases on survival of patients with lung adenocarcinoma. Patients newly diagnosed with lung cancer between 2003 and 2008 were identified from Taiwan National Health Insurance Research Database. Cases with lung adenocarcinoma were further confirmed using the Cancer Registry Database and followed up until the end of 2010. Cox proportional hazard regression was used to calculate the hazard ratio (HR) of coexisting asthma, COPD, and/or TB to estimate all-cause mortality risk. During the study period, 13, 399 cases of lung adenocarcinoma were identified. The HRs of adenocarcinoma in men and women were 1.20 (95% confidence interval [CI], 1.10–1.30) and 1.05 (95% CI, 0.95–1.16), respectively, for individuals with asthma, 1.32 (95% CI, 1.16–1.51) and 0.97 (95% CI, 0.89–1.05), respectively, for COPD, and 0.99 (95% CI, 0.93–1.06) and 1.06 (95% CI, 0.86–1.32), respectively, for individuals with TB. Specifically, among men with coexisting pulmonary diseases, the HRs were 1.63 (95% CI, 1.25–2.13), 1.31 (95% CI, 1.08–1.59), and 1.23 (95% CI, 1.11–1.36) for individuals with asthma + COPD + TB, asthma + COPD, and COPD + TB, respectively. However, there was no increase risk of mortality among women with coexisting pulmonary diseases. Coexisting pulmonary diseases are at an elevated risk of mortality among male patients with lung adenocarcinoma. Such patients deserve greater attention while undergoing cancer treatment.